Teologi kekuasaan: Sebuah Pendekatan Metanaratif bagi Gereja dan Ruang Publik Indonesia - Silvia Wiguno (STT Reformed Injili Internasional, 2026)
This article examines the meaning and purpose of power by focusing on the calling of those who hold authority to reflect God’s reign. In the Indonesian context, where power is shaped by patronage, hierarchy, and respect for authority, it argues that power is not merely a matter of public ethics but a theological issue concerning the church’s understanding of God, humanity, and its calling. Within the biblical metanarrative, the author employs a biblical-theological approach combined with public theology ethics to analyze how God’s mandate of power, given at creation, was distorted by the Fall, redirected through Christ’s redemption, and oriented toward the restoration of creation under Christ’s reign. The article argues that power, in ecclesial and public spheres, is never neutral but always stands under Christ’s sovereignty. Therefore, the faithful exercise of power must be relational, accountable, and oriented toward justice and human dignity. In dialogue with the Indonesian context, it argues that criticism of power is not a threat to harmony but an expression of faithfulness to Christ’s reign moving toward the restoration of all things. Therefore, a theology of power rooted in the biblical metanarrative offers a framework for church to engage critically and responsibly in public life.